Engaging democracy or reinforcing base? A thematic analysis of Desak Anies - Daffa, Ghozi Kamaluddin; Nasvian, Moch Fuad; Effendi, Tonny Dian; Farrasy, Marco Trisna Omar (Jurnal Kajian Komunikasi, 2025)
Background: In the 2024 election, Anies Baswedan used YouTube as a platform to live-stream his campaign titled ‘Desak Anies,’ with an open discussion. The campaign aimed to restore democracy and bring political discourse to the public. Purpose: This research mapped the interactions of netizens in the comment section of the live-streamed “Desak Anies” broadcast on his official YouTube channel. Methods: It employed thematic analysis. Data was collected using the ‘Google Apps Script’ tool, capturing YouTube comments from 13 episodes of ‘Desak Anies.’ The dataset included only direct comments, excluding replies, with a total of 6,996 comments. Result: The comments were mapped into three main themes: supportive comments, which were the most numerous; hateful comments, which were the fewest; and neutral. Conclusion: This study found a large number of supportive comments, with minimal opposition, indicating that “Desak Anies” strengthened Anies Baswedan’s existing support base but failed to attract new supporters. Thus, it creates the echo chamber effect and filters bubbles, preventing the campaign content from reaching broader viewers. Implications: Social media campaigns, such as “Desak Anies”, could potentially engage audiences. However, they often reinforce existing political beliefs, creating echo chambers that limit democratic discourse. Despite the campaign’s intention to foster political engagement, it strengthens existing support for Anies Baswedan and hinders the outreach to undecided or opposing voters. This suggests that digital platforms may inadvertently stifle true democratic deliberation by limiting exposure to diverse perspectives.